METODE LANGSUNG KALKULUS VARIASI PADA ELEKTROMAGNETIKA DALAM WAKILAN FORMA DIFERENSIAL - , I G N Yudi Handayana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lagrangian formalism of electromagnetism has been represented in term of differential forms. The existence of solutions of Maxwell equations is studied in the framework of the direct methods of calculus of variations in the differential forms representation. The purpose of this study is to investigate the existence of minimizer for electromagnetism functional in differential forms representation on the R 4 . The application of direct methods of calculus of variations on the electromagnetism functional shows that the solutions of the Maxwell equations exist in the open and bounded region of â¦ â R 4 , although there is need any constraint to ensure non-negativity the value of Lagrangian density. This study can be used as a basis for the study of electromagnetism and direct method of calculus of variations in general form, as in manifolds.